Analisis Wacana Kritis Polemik UU TNI yang Dikonstruksi melalui Pandangan Al Araf dan Ferry Irwandi pada Podcast Akbar Faizal Uncensored - Rizky, Yafet Punta; Indriastuti, Yudiana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The revision of the 2025 TNI Law raises concerns about expanding military authority into civilian domains and weakening civilian supremacy. The Akbar Faizal Uncensored podcast serves as a discursive arena for public criticism of these developments. This study employs Van Dijk’s Critical Discourse Analysis covering text, social cognition, and social context using document study and note-taking techniques. The discourse centers on the theme “The TNI Law for Generals,” supported by diction, argumentation, and rhetorical strategies. Informants’ social cognition reflects a pro-democracy perspective, while the social context underscores the role of digital media in facilitating state critique. Findings reveal risks of strengthening OMSP, reviving ABRI’s dual function, and restricting civilian space. The analysis highlights the need for a democratic reassessment of the 2025 TNI Law. Academically, the study enriches CDA scholarship in the digital era; practically, it informs policy advocacy and democracy literacy.